2019
DOI: 10.1038/s41597-019-0233-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial high-resolution socio-energetic data for municipal energy system analyses

Abstract: In the context of the energy transition, municipalities are increasingly attempting to exploit renewable energies. Socio-energetic data are required as input for municipal energy system analyses. This Data Descriptor provides a compilation of 40 indicators for all 11,131 German municipalities. In addition to census data such as population density, mobility data such as the number of vehicles and data on the potential of renewables such as wind energy are included. Most of the data set also contains public data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Clusters 3, 4, 7 and 8, on the other hand, show a high potential for renewable energies and Cluster 9 comprises all German municipalities without inhabitants. The indicators and resulting clusters are published open access in Weinand et al (2019b) and this dataset can support in answering a wide range of energy related research challenges.…”
Section: Resultsmentioning
confidence: 99%
“…Clusters 3, 4, 7 and 8, on the other hand, show a high potential for renewable energies and Cluster 9 comprises all German municipalities without inhabitants. The indicators and resulting clusters are published open access in Weinand et al (2019b) and this dataset can support in answering a wide range of energy related research challenges.…”
Section: Resultsmentioning
confidence: 99%
“…69 In the cluster analysis 23 and the regression in this study, the onshore wind potentials are taken from McKenna et al, 28 where the potential is estimated for Germany by matching wind turbines to land use and wind speed classes. When onshore wind potentials in all German municipalities are discussed in the main text of this present article, they are based on McKenna et al 28 The indicators and clusters were published open access in Weinand et al 70 The cluster analysis in Weinand et al 23 indicated that the German municipalities are heterogeneous in terms of size and socio-energetic indicators. "Socio-energetic" indicators refer to social indicators (such as age of persons and buildings, or ownership) that can have an indirect influence on an energy system (e.g., by influencing energy service demands) as well as indicators that have a direct influence on an energy system, such as RE generation potentials.…”
Section: Case Studymentioning
confidence: 99%
“…Empirical analyses for the current state of DH on the country-level have been conducted before, e.g. for Germany, Triebs et al, 2021 [4] analysed the fuel input on the network level, and Weinand et al, 2019 [5] published an open dataset on the share of buildings with DH for the municipalities based on the census 2011. However, only a few studies have analysed the current spatial extension of DH on the country-or EU-level, mostly due to lack of data.…”
Section: State Of Researchmentioning
confidence: 99%